Netherton Syndrome with a Novel Likely Pathogenic Variant c.420del (p.Ser141ProfsTer5) in SPINK5 Gene: A Case Report - Katya Kovacheva; Zornitza Kamburova; Preslav Vasilev; Ivelina Yordanova (Karger Publishers, 2024)
Introduction: Netherton syndrome (NS) is a rare autosomal recessive genodermatosis in the group of congenital ichthyosis. The clinical manifestations of the syndrome vary from a very mild clinical manifestation occurring with the picture of ichthyosis linearis circumflexa to exfoliative erythroderma. It can be fatal in the first days of a newborn's life due to dehydration, hypothermia, weight loss, respiratory infections, and sepsis. A specific anomaly of the hair trichorrexis invaginata is considered pathognomonic for the syndrome. Genetic testing of SPINK5 gene is key to confirming the diagnosis and starting early treatment. Case Presentation: We present a case report of NS in a 6-year-old boy who suffered from generalized erythroderma and desquamation of the skin from birth. The patient has atopic diathesis, recurrent skin infections, increased levels of IgE, and delayed physical development. Two genetic variants in SPINK5 gene with clinical significance were identified. The first detected variant is a nonsense mutation, predicted to cause loss of normal protein function either by protein truncation or by nonsense-mediated mRNA decay. The second variant is a likely pathogenic frameshift mutation that truncates the protein in 5 amino acids. The child was treated with acitretin, without satisfactory effect. Conclusion: The genetic variant we have described correlates with a severe clinical phenotype of NS. The second genetic variant of the SPINK5 gene, inherited from the father in our case, is novel and has never been published in the literature.